Which is more important for the intensity of intra-amniotic inflammation between total grade or involved anatomical region in preterm gestations with acute histologic chorioamnionitis? - Park, Chan-Wook (Korean Society of Obstetrics and Gynecology; Korean Society of Contraception and Reproductive Health; Korean Society of Gynecologic Endocrinology; Korean Society of Gynecologic Endoscopy and Minimal Invasive Surgery; Korean Society of Maternal Fetal Medicine; Korean Society of Ultrasound in Obstetrics and Gynecology, 2013)
OBJECTIVE: There is no data on which is more important for the intensity of intra-amniotic inflammation (IAI) between total grade or involved anatomical region in acute histologic chorioamnionitis (acute-HCA) of preterm-gestations. The objective of current study is to examine this issue. METHODS: The intensity of IAI was measured by amniotic fluid (AF) white blood cell (WBC) count and matrix metalloproteinase-8 (MMP-8) concentration in 225 singleton preterm-gestations (<36 weeks) who had acute-HCA including chorio-decidua involvement and delivered within 5 days of amniocentesis. Acute-HCA was defined in the presence of acute inflammatory changes in each anatomical region (i.e., chorio-decidua, amnion or chorionic plate). Patients were divided into 6 groups according to total grade (i.e., 1-6) and the presence or absence of chorio-decidua restriction (i.e., chorio-decidua restriction vs. extension beyond chorio-decidua) of acute-HCA. RESULTS: There was no significant difference in a median AF WBC and MMP-8 between the two groups (group-1, cases with total grade 1 vs. group-2, cases with total grade 2) among cases with chorio-decidua restriction (each for P>0.05) and between the four groups (group-3, cases with total grade 2 vs. group-4, cases with total grade 3 vs. group-5, cases with total grade 4 vs. group-6, cases with total grade 5-6) among cases with extension beyond chorio-decidua (each for P>0.05). However, group-3 (cases with extension beyond chorio-decidua) had a significantly higher median AF WBC and MMP-8 than group-2 (cases with chorio-decidua restriction) among cases with total grade 2 (each for P<0.05). CONCLUSION: Involved anatomical region is more important than total grade for the intensity of IAI in acute-HCA of preterm-gestations.